Enhancing Long-term Memory Through Keeping Vocabulary Records Strategy in an Islamic Higher Education: (Meningkatkan Daya Ingat Jangka Panjang melalui Strategi Pencatatan Kosakata di Perguruan Tinggi Islam) - Hasanah, Uswatun; Hidayah, Siti Nurul (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2025)
Improving vocabulary mastery in English can be challenging for some students, especially for learners who predominantly speak Javanese and are learning English as a second language. This research focuses on employing keeping vocabulary record strategies to enhance students' vocabulary mastery at STIT Sunan Giri Trenggalek during the academic year 2024-2025, highlighting the uniqueness and distinctive characteristics of these strategies. The study utilizes a classroom action research approach, which includes two cycles of quantitative and qualitative data collection. For quantitative analysis, students' test scores were gathered, while qualitative data was collected through observations, questionnaires, and interviews. This data was then examined using descriptive analysis, supplemented by insights from the qualitative data. The results indicate significant progress among students in their long-term retention of vocabulary proficiency. In particular, students' vocabulary retention improved by up to 22% across various aspects, including spelling, pronunciation, meaning, and use. Additionally, the implementation of these strategies has fostered a more interactive and positive classroom environment. To further enhance their learning, students are encouraged to practice these strategies outside of class and explore a variety of vocabulary resources.